Premix Based on Taro Flour (Colocasia esculenta) with the Addition of Breadfruit Flour (Artocarpus altilis) - Putri Sari; Asri Widyasanti (Indonesian Journal Publisher, 2026)
This study aimed to obtain the optimal formulation of a gluten-free waffle premix based on taro flour (Colocasia esculenta) with the addition of breadfruit flour (Artocarpus altilis) and to evaluate its physicochemical characteristics and consumer acceptance. The research was conducted using a Completely Randomized Design with a single factor, consisting of four formulation ratios of taro flour to breadfruit flour, namely 100:0, 75:25, 50:50, and 25:75, with three replications for each treatment. Physicochemical analyses were performed on the waffle premix, including moisture content using the oven-drying method, particle fineness through sieve analysis and fineness modulus determination, and color measurement using a colorimeter based on the CIELAB system (L*, a*, b*). Sensory evaluation was carried out through a hedonic test using untrained panelists to assess color, aroma, taste, texture, and overall acceptance of the resulting waffles. The results showed that differences in flour formulation significantly affected moisture content, particle fineness, and color characteristics of the gluten-free waffle premix (p < 0.05). Moisture content values of all formulations were below the maximum standard for flour-based products, indicating good storage stability. Increasing the proportion of breadfruit flour tended to reduce brightness (L*) and increase yellowness (b*). Based on hedonic test results, the formulation with an equal ratio of taro flour and breadfruit flour (50:50) obtained the highest scores for taste, texture, and overall acceptance. These results indicate that the 50:50 formulation represents the optimal gluten-free waffle premix and has potential for further development as a locally based functional food product.